Sierra Leone : Request for Disbursement under the Rapid Credit Facility. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2021)
Sierra Leone continues to grapple with the serious and persistent economic and social effects of the pandemic. Containment measures and trade disruptions in 2020 weakened domestic demand and exports and caused domestic revenues to fall. Moreover, food insecurity has risen from its already-high pre-COVID-19 level. 2021 is set to be another challenging year, with the 'second wave' of infections and vaccine-related uncertainties posing further risks to the recovery. As import growth picks up and development partner support returns to pre-2020 levels, Sierra Leone faces urgent external and fiscal financing needs (both around about 2 percent of GDP). Uncertainty about the outlook and larger near-term financing gaps have impeded the immediate resumption of the program under the Extended Credit Facility (ECF). The authorities are therefore requesting a disbursement under the Rapid Credit Facility (RCF) of 17 percent of quota (SDR 35.26 million). This follows the June 2020 RCF (50 percent of quota or SDR 103.7 million) and would bring total access for the past 12-month period to 82 percent of quota (or 5 1\2 percent of GDP), well within the 150 percent of quota annual PRGT access limit. The authorities also received debt relief under the Catastrophe Containment and Response Trust (CCRT) and are participating in the Debt Service Suspension Initiative (DSSI).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet